2017
DOI: 10.1016/j.healun.2017.02.025
|View full text |Cite|
|
Sign up to set email alerts
|

In vitro and in vivo evaluation of a novel integrated wearable artificial lung

Abstract: Background Conventional ECMO is cumbersome and is associated with high morbidity and mortality. We are developing the Paracorporeal Ambulatory Assist Lung (PAAL), designed to ambulate lung failure patients during bridge to transplant or recovery. In this study, we investigated the in-vitro and acute in-vivo performance of the PAAL. Methods The PAAL features a 1.75 inch diameter cylindrical HFM bundle of stacked sheets, with a surface area of 0.65 m2 integrated with a centrifugal pump. The PAAL was tested on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 23 publications
(32 reference statements)
0
28
0
Order By: Relevance
“…This prototype device weighs 1850 g and is intended to have the option to be worn by the patient. The specific design and manufacturing details of the LF-PAL devices have been previously published [ 22 ]. The device has previously been evaluated for high-flow adult oxygenation [ 22 ], but not for low-flow CO 2 removal.…”
Section: Methodsmentioning
confidence: 99%
“…This prototype device weighs 1850 g and is intended to have the option to be worn by the patient. The specific design and manufacturing details of the LF-PAL devices have been previously published [ 22 ]. The device has previously been evaluated for high-flow adult oxygenation [ 22 ], but not for low-flow CO 2 removal.…”
Section: Methodsmentioning
confidence: 99%
“…9). 44 The stacktype fiber bundles and the impellers with embedded magnets allow the miniaturized profile. In vitro and in vivo testing has demonstrated that the paracorporeal ambulatory assist lung generated flows of 3.5 L/min at rotational speed of 2,100 revolutions/min and provided sufficient O 2 and CO 2 transfer.…”
Section: Wearable Ecmomentioning
confidence: 99%
“…Risk and complications can be substantially alleviated by integrating the pump and oxygenator together into one device 75 . The Pittsburgh Ambulatory Assist Lung (PAAL) is based on oxygenation efficiency modeled as a function of fiber bundle diameter 20,74 . Using the model, a 1.75‐mm‐diameter bundle with a 0.65‐m surface area was predicted to produce oxygenation of 180 mL/min at blood flow rate of 3.5 L/min.…”
Section: Wearable Artificial Lung Systems Allow For Ambulationmentioning
confidence: 99%